Recurrent Hemoptysis with Penicillium Marneffei and Stenotrophomonas Maltophilia in Job’s Syndrome - Bosco HM Ma; Calvin SH Ng; Rebecca KY Lam; Song Wan; Innes YP Wan; Tak Wai Lee; Anthony PC Yim (Canadian Respiratory Journal)
Pulmonary infection caused by the opportunistic organisms Penicillium marneffei and Stenotrophomonas maltophilia in patients with Job’s syndrome is rare and not well documented. The case of a 30-year-old man with Job’s syndrome who developed recurrent pneumonia and lung abscesses caused by P marneffei and S maltophilia, complicated by massive hemoptysis, is described. Bronchial artery embolization was successful in controlling the hemoptysis; however, the infection proved fatal despite appropriate antimicrobial therapy. A brief review of the literature on Job’s syndrome and its associated infective pulmonary manifestations is also presented.